Antimicrobialsusceptibilityof bacteria isolated from goats with subclinical mastitis in the Southern Marmara region of Turkey - Goncagül, Gülşen; Cokal, Yavuz; Gunaydin, Elcin (Medycyna Weterynaryjna - Redakcja, 2021)
The mastitis of dairy goats is a disease of the economic importance worldwide and is mostly associated with bacterial infections. The aim of this study was to isolate the bacteriae causing subclinical mastitis, and determine to the susceptibility of some clinical isolates against several antimicrobial agents frequently used to control bacterial subclinical mastitis in dairy goats in the Southern Marmara Region. A total of 68 Saanen goats were used for this investigation and subclinical mastitis was determined by using California Mastitis Test. As a result of bacteriological analysis of milk samples, 30 different bacteria species have been identified and non-aureus staphylococci found to be the predominant bacteria species with the rate of 22.1%. The species with the highest isolation rate among the isolates were Escherichia coli (18.9%), Staphylococcus aureus (15.7%), Streptococcus agalactiae (14.2%) and Staphylococcus epidermidis (7.9%). The antimicrobial susceptibility of the high isolation rate species including Escherichia coli, Staphylococcus aureus, Streptococcus agalactiae, Staphylococcus epidermidis, Streptococcus uberis, Enterococcus faecalis, Staphylococcus haemolyticus and Mannheimia haemolytica to twelve antibiotics were determined by disc diffusion method. Bacterial strains analyzed showed highest sensitivity to ofloxacin (87.9%) and followed by cefuroxime (85.8%) and cefazolin (83.6%). In conclusion, subclinical mastitis still remains a problem in dairy goats, and for the elimination of subclinical mastitis, besides protective measures, determination of the bacteriae causing mastitis and their antibiotic sensitivities should be priority.
Keywords: 2. Zero hunger; 6. Clean water; 3. Good health